Human Talent and Customer Satisfaction in the hotels of the city of Tulcán - Quizhpi López, Anderson Paul; Guevara Guevara, Elizabeth Josefina (Tierra Infinita, 2024)
This current study examined the relationship between human talent management and customer satisfaction in hotels spotted in Tulcán. A quantitative approach was employed, putting into use two distinct surveys: one directed at the staff of each hotel and the other at the clients. To assess customer satisfaction, the Net Promoter Score (NPS) was used. The data was processed using the SPSS software, which also facilitated the correlation analysis between the two variables via the Chi-square test. The findings indicated that over 50% of the processes related to human talent management, including organization, development, reward, retention, and audit, were satisfactorily met, though the integration process lagged behind. In terms of customer satisfaction, the NPS score reached 60.5%, reflecting a significant improvement from the previous year’s 33%. Lastly, the Chi-square test confirmed a connection between human talent management and customer satisfaction in Tulcan’s hotels.